Fashionable queerness : straight appropriation of queer fashion - Bollas, Angelos (Emerald Publishing Limited, 2024)
The exploration of masculinity in celebrity culture sheds light on the complex interplay between gender norms, media influence, and the construction of modern masculinity. Timothée Chalamet, Paul Mescal, and Barry Keoghan whose unique approach to fashion, style, and self-presentation challenges traditional notions of masculinity, provide fruitful subject matter for deep analysis. In Fashionable Queerness: Straight Appropriation of Queer Fashion, author Angelos Bollas weaves together gender theory, sexuality studies, and celebrity research to create fresh pathways of understanding. Through this nuanced exploration, Bollas focuses on the intricate connections between gender dynamics, sexuality, and celebrity culture. From the red carpet to glossy fashion magazines, Timothée Chalamet, Paul Mescal, and Barry Keoghan, rising stars known for their acting prowess, have become icons for their distinctive fashion choices and their blurring of gender boundaries. By analyzing how Chalamet, Mescal, and Keoghan navigate the norms of celebrity culture, Bollas provides insights into how masculinity is both reinforced and transformed in the public eye. Bollas unravels the complexities of how gender and sexual identity and representation intersect with the construction of celebrity personas. Examining representations of masculinity in celebrity culture and uncovering broader societal implications related to gender norms, this is valuable reading for scholars of Gender Studies, Media and Communication, Fashion and Style, Cultural Capital Theory, and Queer Studies.
Includes index.
Keywords: Masculinity in popular culture.; Social Science -- Gender Studies.; Gender studies: men and boys.; Gender studies, gender groups.; elektronické knihy; electronic books